2020
DOI: 10.1101/2020.05.15.098731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Favipiravir strikes the SARS-CoV-2 at its Achilles heel, the RNA polymerase

Abstract: The ongoing Corona Virus Disease 2019 pandemic, caused by severe 20 acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has emphasized the urgent need for antiviral therapeutics. The viral RNA-dependent-RNA-polymerase (RdRp) is a promising target with polymerase inhibitors successfully used for the treatment of several viral diseases. Here we show that Favipiravir exerts an antiviral effect as a nucleotide analogue through a combination of chain termination, slowed RNA synthesis and lethal mutagenesis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(120 citation statements)
references
References 49 publications
2
113
1
4
Order By: Relevance
“…Using VeroE6 cells and an antiviral assay based on reduction of cytopathic effect (CPE), we recorded EC50 and EC90 of 32 and 52.5 µg/mL using a multiplicity of infection (MOI) of 0.001, 70.0 and >78.5µg/mL with an MOI of 0.01 ( Figure S1) in accordance with previous studies [18][19][20] . Infectious titer reductions (fold change in comparison with untreated cells) were ≥2 with 19.6µg/mL of favipiravir and ranged between 11 and 342 with 78.5µg/mL.…”
Section: In Vitro Efficacy Of Favipiravirsupporting
confidence: 87%
See 2 more Smart Citations
“…Using VeroE6 cells and an antiviral assay based on reduction of cytopathic effect (CPE), we recorded EC50 and EC90 of 32 and 52.5 µg/mL using a multiplicity of infection (MOI) of 0.001, 70.0 and >78.5µg/mL with an MOI of 0.01 ( Figure S1) in accordance with previous studies [18][19][20] . Infectious titer reductions (fold change in comparison with untreated cells) were ≥2 with 19.6µg/mL of favipiravir and ranged between 11 and 342 with 78.5µg/mL.…”
Section: In Vitro Efficacy Of Favipiravirsupporting
confidence: 87%
“…This inhibits RNA strand extension and induces abnormal levels of mutation accumulation into the viral genome 16,17 . Recently, it was shown in vitro that favipiravir has a similar mechanism of action with SARS-CoV-2 through a combination of chain termination, reduced RNA synthesis and lethal mutagenesis 20 . Our genomic analysis confirmed the mutagenic effect of favipiravir in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agent could bind to RdRp proteins and could inhibit genome replication. A previous report showed that the agent inhibits SARS-CoV-2 in vitro [ 28 ]. This study suggests that inhibition of genome replication is termination [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that the agent inhibits SARS-CoV-2 in vitro [ 28 ]. This study suggests that inhibition of genome replication is termination [ 28 ]. However, detailed molecular interactions between the agent and the viral replication systems may not currently be known.…”
Section: Discussionmentioning
confidence: 99%